EaaS: Available yet hidden infrastructure inside MSE - Joseph Ng, P.S. (Association for Computing Machinery, 2016)
Information technology infrastructure investment is a central issue for Malaysia medium size enterprises facing scarcity resource during economic turbulence. In this paper, we propose a costeffective resource pooling capacity building the solution that optimizes on demand service. Further, we examine the suitability of legacy theories for a commodity of IT infrastructure and disruptive technology. Our argument opens up a helicopter angle of the strategic investment correlation between the proposed consolidated infrastructure features and important organizational variables for economic sustainable. The research was conducted via survey questionnaire with data compiled from 100 respondents in Peninsular Malaysia and is to test-retest the reliability of the previous 122 respondents for information consistency. The findings of the research ascertain that un-optimized and unreusabilities of existing desktop are two significant determinants of infrastructure investment. Our findings further show that inefficient utilization gap is a distal determinant of investment, exerting its influence indirectly from the over investment and over budget. The analysis lead us to propose an organic rapid elasticity infrastructure service that will grow or shrink with the business performance. We discuss the contribution of the research findings for Exostructure as a Service framework while concluding the urgent need to revitalize the computing requirements. Â© 2016 ACM.